Prognosis of colorectal cancer, prognostic index of immunogenic cell death associated genes in response to immunotherapy, and potential therapeutic effects of ferroptosis inducers - Lei, Mengjie; Xiao, Meihua; Long, Zhiqing; Lin, Taolin; Ding, Ran; Quan, Qi (Frontiers in Immunology, 2024)
This study harnesses the extensive resources of bioinformatics and medical big data to seamlessly integrate datasets from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA), offering a comprehensive glimpse into the intricate expression landscapes of immunogenic cell death (ICD)-related genes in colorectal cancer (CRC). Employing meticulous differential expression analysis and sophisticated bioinformatic approaches, we have not only discerned distinct expression profiles of ICD genes within CRC tissues but also unveiled the underlying molecular pathways and intricate gene networks, thereby laying a robust foundation for subsequent investigations.Building upon this, unsupervised consensus clustering analysis further refined the CRC patient cohort into unique ICD-associated subtypes, each characterized by distinct clinical and immunological features. In-depth immune microenvironment analysis and single-cell RNA sequencing provided unprecedented insights, revealing profound variations in immune responses and cell infiltration patterns across these subtypes.Crucially, our study delves deeply into the therapeutic potential of ICD-related genes, particularly within the realm of emerging cell death inducers. Experimental validation robustly confirmed the direct impact of these agents on ICD gene expression, reinforcing their clinical relevance. Notably, we interrogated the response of ICD genes to ferroptosis inducers, in conjunction with other clinical drugs in combinatorial therapies, furnishing actionable insights into their efficacy and the intricate regulatory mechanisms governing CRC drug sensitivity and resistance.Our findings not only fortify the scientific rationale for developing precision medicine strategies targeting ICD genes but also offer invaluable guidance for the clinical translation of novel cell death-inducing therapies. With continued validation and drug development efforts, these discoveries hold the promise of revolutionizing CRC management, paving the way for more personalized treatment strategies and ultimately enhancing patient outcomes.